2020
DOI: 10.1038/s41419-020-2726-3
|View full text |Cite
|
Sign up to set email alerts
|

HMGA2 regulates circular RNA ASPH to promote tumor growth in lung adenocarcinoma

Abstract: In this study, we identified a circular form of ASPH RNA (circASPH), expression of which was upregulated in lung adenocarcinoma and the human lung adenocarcinoma cell lines. We also found a positive correlation between circASPH level and the T and N stages of lung adenocarcinoma patients. Patients with higher levels of circASPH had a shorter overall survival. Moreover, we demonstrated that circASPH was directly regulated by HMGA2 and Twist1. The direct positive regulation of circASPH by Twist1 was dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…ASPH has recently been shown to promote BC development and metastasis by activating the Notch cascade [ 11 ]. ASPH is also overexpressed and strongly correlated with tumor invasiveness and poor prognosis in various tumor types, including colorectal [ 12 ], hepatocellular [ 13 ], non-small cell lung [ 14 ], pancreatic [ 15 17 ], and prostate cancer [ 18 ], and cholangiocarcinoma [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASPH has recently been shown to promote BC development and metastasis by activating the Notch cascade [ 11 ]. ASPH is also overexpressed and strongly correlated with tumor invasiveness and poor prognosis in various tumor types, including colorectal [ 12 ], hepatocellular [ 13 ], non-small cell lung [ 14 ], pancreatic [ 15 17 ], and prostate cancer [ 18 ], and cholangiocarcinoma [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic relevance of circNETO2 may be limited as the diagnostic accuracy was moderate in our study (AUC = 0.705); circNETO2 has not been studied in RCC by other researchers so far. In lung cancer cells, circNETO2 expression was not different in normal and cancerous lung tissue [21].…”
Section: Discussionmentioning
confidence: 82%
“…Due to their stable structure, circRNAs are promised to become a new strategy for LUAD-targeted therapy. Xu et al observed that HMGA2 could regulate circASPH to promote tumor growth in patients with LUAD ( Xu L. et al, 2020 ). The study of Lu G.J.…”
Section: Discussionmentioning
confidence: 99%